Integrasi Artificial Intelligence dan Lembaga Keuangan Syariah di Era Society 5.0: Memandang dari Lensa Kaidah Fikih: Integrasi Kecerdasan Buatan dan Lembaga Keuangan Islam di Era Masyarakat 5.0: Tinjauan dari Perspektif Kaidah Hukum Islam - Muhammad Syarif Hidayatullah; Rahmat Fadillah (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2025)
Artificial Intelligence (AI) first appeared as a product of the Industrial Revolution 4.0. Then, with the advent of the Society 5.0 era, information technology and AI were combined to create harmony between technological developments and enhance human welfare. The existence of AI in the context of human welfare will also be connected to the economy in general and financial institutions in particular, including Islamic financial institutions. This paper aims to explain the integration of AI and Islamic financial institutions in the era of Society 5.0, analyzing it through the lens of Islamic legal maxims. The research method employed normative legal research, utilizing a conceptual approach and an Islamic legal maxims approach. Based on the research discussion, AI could positively contribute to Islamic financial institutions. The integration of technology and Islamic finance was achieved through the use of AI to support the operations of Islamic financial institutions in implementing business management, encompassing services, performance, and risk management. From the lens of Islamic legal maxims, the use of AI by Islamic financial institutions is linked to Islamic legal maxims as guidelines, including the ibâhah principle in muamalah, intention, taisir, sad adz-dzarî'ah, and maslahah rules.